KARAKTERISTIK PERMEN JELLY JANTUNG BUAH NANAS DENGAN VARIASI KONSENTRASI KARAGENAN DAN SUHU PEMANASAN - Giyarto Giyarto; Sony Suwasono; Putri Oktavilia Surya (Faculty of Agricultural Technology, University of Jember, 2019)
Utilization of pineapple waste as by-product of pineapple fruit consumption such as peel, fruit eyes, and the core of the pineapple is still low. The middle part of the pineapple fruit called core has elongated shape, rather hard texture, and slightly of sweet and sour taste. Sweet and sour taste from the pineapple core had good nutritional content, so it enabling to be developed into more economically products, such as jelly candy. Chewy texture, transparent colors, sweetness, and fruity aroma as the jelly candy’s properties are strongly influenced by the gelling components and the temperature processing. The use of right combination between carrageenan concentration, pineapple core, and heating temperature can produced a good quality jelly candy. This research was carried out with Randomized Complete Block Design (RAK) method with two factors, i.e. variations of carrageenan (2%, 3% and 4% (b/v) and heating temperature (70°C, 80°C, 90°C). The aims of the research were to known characteristic of pineapple core jelly candy and determined the best formulation of it based on pishical, chemical and organoleptic characteristic. The result showed that the variation of 3% carrageenan and cooking temperature of 90°C was the best formulation of the pineapple core jelly candy with an effectiveness value of 0.66. It has texture value of 376.47 ± 0.71 g/mm; moisture content of 16.16 ± 0.37%; ash content of 1.26 ± 0.24%; vitamin C of 12.80 ± 0.69 mg/100g; reduction sugar of 11.90 ± 0.02%; and sucrose of 28.55 ± 0.24%. Based from organoleptic of jelly candy, the panelists like of texture (4.6), chewy texture (4.76) and rather like of the color (3.76), taste (4.28), aroma (4.04), overall organoleptic (4.12). Keywords: carrageenan, core of the pineapple, cooking temperature, organoleptic